Administrative appeal as a legal process: meaning and role - Persheyev, A.S.; Smanova, A.B.; Biskultanova, A.M. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article explores the importance of social legal awareness development, as well as the provision of Constitutional Law and Administrative Law mechanisms of the right to human rights and freedoms defense. The purpose of the article is the essential role of the administrative complaint concept in society. It analyses legal support process, the subject and the importance of the complaint procedure, when considering appeals by the current State Bodies. The introduction of the administrative appeal procedure in order to increase public confidence in public authorities, including Law Enforcement Agencies in present time, and determine the importance of the administrative complaint process as a process. Ensuring the study of the essential role of Administrative Appeal Law as a process. This article seeks to examine both the mechanisms and procedures of administrative appeal as well as its effectiveness and impact on legal systems. Specific areas for study are legal framework, procedural aspects and practical implementation of administrative appeal. This work plays an invaluable role in understanding justice systems and administrative management, deepening legal knowledge and improving citizen legal defense effectiveness. The analysis has demonstrated the power of administrative appeal as an effective mechanism for protecting citizens' rights and liberties while increasing state bodies' transparency and responsibility. In this article are provided recommendations on improving appeal procedures.